Keefektifan Metode Bernyanyi Materi Bangun Ruang Terhadap Pemahaman Konsep di SD Negeri Kalicari 01 - Nazilah, Hikmatun; Untari, Mei Fita Asri; Subekti, Ervina Eka (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The background underlying this research is the lack of students' understanding in learning mathematics in class five classroom building material at the Kalicari 01 Semarang State Elementary School. This is because post-Covid pandemic learning, teachers still use the lecture method in teaching, students do not understand the learning material, so learning outcomes are low. The aim of this research is to determine the effectiveness of using the audio-visual singing method in building materials on the conceptual understanding of fifth grade students at the Kalicari 01 Semarang State Elementary School. This type of research uses quantitative, Pre Experimental design with the One-Group Pretest-Posttest Design type. The results of the final analysis which was carried out using the t-test showed that tcount > ttable, namely 12.063 > 2.056. The Classical learning completeness test obtained a result of 75%. So the conclusion is that Ho is rejected and Ha is accepted so that the singing method is effective in understanding the concepts of fifth grade students at Kalicari 01 Semarang State Elementary School.